2014
DOI: 10.1097/aog.0000000000000290
|View full text |Cite
|
Sign up to set email alerts
|

Mifepristone and Oral, Vaginal, or Sublingual Misoprostol for Second-Trimester Abortion

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 16 publications
3
28
3
Order By: Relevance
“…There was no difference in the prevalence of gastrointestinal side effects between the two groups. Nearly all the women in our study aborted before 24 h like in other similar studies conducted by Elami et al [5], Dickinson et al [6], Borgatta and Kapp [7] reported a success rate of 95 % within 24 h. In our study, the success rate was 89 % in Group-I and 96 % in Group-II (Table 1). …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…There was no difference in the prevalence of gastrointestinal side effects between the two groups. Nearly all the women in our study aborted before 24 h like in other similar studies conducted by Elami et al [5], Dickinson et al [6], Borgatta and Kapp [7] reported a success rate of 95 % within 24 h. In our study, the success rate was 89 % in Group-I and 96 % in Group-II (Table 1). …”
Section: Discussionsupporting
confidence: 84%
“…A detailed history was taken, clinical examination including gynecological examination and ultrasonography was performed. The inclusion criteria were: (1) women aged more than 18 Years, (2) singleton pregnancy, (3) closed cervical os, (4) no vaginal bleeding, (5) a legal indication for termination of pregnancy and official approval, (6) willing to follow the study protocol and provide informed consent and (7) willing to undergo required follow-up and surgical management when indicated.…”
Section: Methodsmentioning
confidence: 99%
“…The low rates of side effects and short bleeding period observed in our study is likely attributable to our use of a low dosage, and perhaps also to the sublingual administration route employed. Sublingual administration of misoprostol is advantageous in that it precludes the inconvenience of vaginal administration and also avoids the first‐pass liver effects that are associated with oral administration, while enabling rapid pregnancy termination …”
Section: Discussionmentioning
confidence: 99%
“…Even though oral administration is appealing for several reasons like convenient and lack of invasiveness, vaginal route seems to be more advantageous (Dickinson JE, 2014). 7 Another study by Elami-Suzin compares the efficacy of mifepristone plus misoprostol and mifepristone plus oxytocin; also confirms vaginal misoprostol has least side effects and convenient.…”
Section: Discussionmentioning
confidence: 99%
“…7 Another study by Elami-Suzin compares the efficacy of mifepristone plus misoprostol and mifepristone plus oxytocin; also confirms vaginal misoprostol has least side effects and convenient. 8 A study by MacIsaac revealed the absorption kinetics of misoprostol with a dose of 400 µgms compared between oral administration and vaginal treatment.…”
Section: Discussionmentioning
confidence: 99%